Nilai Resistivitas dan Durabilitas Batu Lempung dan Batu Pasir pada Proyek Pembangunan Bendungan Jragung - Arisanto, Pranu; Sasangka, Daru Jaka; Patiroi, Andi; Riyanto, Didit Puji; Prasetyo, Wahyu; Dinggatanta, Dinggatanta (Universitas Batanghari Jambi, 2025)
Each type of rock has different resistivity values as well as durability. Continuous geoelectrical data is highly beneficial for estimating the distribution of rocks based on their resistivity values. The purpose of this study is to observe the resistivity patterns of each rock unit, both subsurface and exposed in the field, where each rock unit has specific durability values. The geoelectrical survey was conducted using the Dipole-Dipole and Wenner-Schlumberger methods with the Multichannel Resistivity MAE X 612 EM+ instrument. A case study was carried out at one of the excavation sites at Jragung Dam, with lithology consisting of sandstone and claystone of varying thicknesses. Claystone was identified as a weaker rock with lower durability compared to sandstone. The durability of claystone ranges from 18% to 60%, while the durability of sandstone exceeds 80%. Based on geoelectrical measurements using the Dipole-Dipole and Wenner-Schlumberger methods, as well as data processing with ERT LAB and Res2DINV software, sandstone generally has a resistivity of more than 18 Ohm.m, while claystone has a resistivity of 0–18 Ohm.m. It was observed that the resistivity values of claystone and sandstone are proportional to the durability of the rocks. The better the rock durability, the higher the resistivity value.